2018
DOI: 10.1186/s13020-018-0217-6
|View full text |Cite
|
Sign up to set email alerts
|

Metabonomic study of the protective effect of Fukeqianjin formula on multi-pathogen induced pelvic inflammatory disease in rats

Abstract: BackgroundFukeqianjin formula has been effectively used in the treatment of pelvic inflammatory disease (PID) and the related complications in clinic. Although there have been some studies about the underlying mechanism that focus on its anti-inflammatory and immunoregulatory activities. But the mechanism is still not fully understood. The aim of this study was to investigate the alteration of plasma metabolic profiles in PID rats and the regulatory effect of Fukeqianjin formula on potential biomarkers.Methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 56 publications
1
13
0
Order By: Relevance
“…Metabolomics can characterize the dynamic changes of metabolites throughout the biological system providing a powerful platform for discovering new biomarkers and biochemical pathways [15, 16], improving diagnosis [17], treatment and prediction [18, 19] in complex systems. Although some studies have analyzed the metabolites of AR in vivo, only the changes of endogenous metabolites of AR from different habitats in normal mice for quality evaluation were compared [5, 20].…”
Section: Introductionmentioning
confidence: 99%
“…Metabolomics can characterize the dynamic changes of metabolites throughout the biological system providing a powerful platform for discovering new biomarkers and biochemical pathways [15, 16], improving diagnosis [17], treatment and prediction [18, 19] in complex systems. Although some studies have analyzed the metabolites of AR in vivo, only the changes of endogenous metabolites of AR from different habitats in normal mice for quality evaluation were compared [5, 20].…”
Section: Introductionmentioning
confidence: 99%
“…TCM including compound and monomer keeps getting more attention due to its multiple biological activities, such as anti-inflammation, antioxidant, and immunity enhancement, especially its non-tolerance to bacteria and virus (24,25). A lot of studies showed that TCM was effective in preventing organisms from a bacterial infection (26). For these reasons, many researchers are focused on the positive effect of TCM on preventing and treating endometritis of dairy cows, but few studies aimed at the preventive and therapeutic effects of TCM on sheep endometritis.…”
Section: Discussionmentioning
confidence: 99%
“…To standardise the application of Chinese patent medicine in the treatment of PID, the Chinese Association of Chinese Medicine (CACM) promulgated the Clinical Practice Guideline on Traditional Chinese Medicine Alone or Combined with Antibiotics for Patients with Pelvic Inflammatory Disease in 2017. A metabolomics study revealed that FKQJ had the efficacy of potential therapeutic to multiple pathogens induced PID by reducing inflammation and improving metabolic disorders [ 42 ]. Although the adjuvant treatment of PID with traditional Chinese medicine has clinical efficacy, its mechanism and safety are also worthy of attention.…”
Section: Discussionmentioning
confidence: 99%